ANALYSIS OF SOCIAL EMOTIONAL DEVELOPMENT IN EARLY CHILDREN THROUGH TRADITIONAL GAMES - Riskayanti, Neni; Budi, Bartolomius; Bonai, Oktaf Diana (Journal of Early Childhood Education (JECE), 2023)
The purpose of this research is to analyze the socio-emotional development of children engaged in the traditional game of ma’batu in Lembang Makkodo, Simbuang District. This study employs qualitative research methods, narrating the results of observations, interviews, and field studies conducted. The theoretical framework used is based on Parten's stages of play, adapted to early childhood education curriculum guidelines outlined in Permendikbud 146/2014 concerning children's developmental milestones. Findings from this research indicate that ma’batu, as a type of traditional game, holds values such as cooperation, communication, self-awareness, responsibility towards oneself and others, and prosocial behaviors such as patience while waiting for turns, managing disappointment when the team loses, enthusiasm, independence, and interest in the game. Consequently, these elements stimulate and develop the socio-emotional aspects of early childhood. Ma’batu games are suitable for children as young as three years old.